Active Sites Determination and De-aggregation of Detonation Nanodiamond Particles - Muhammad Khan (Science Faculty of Chiang Mai University, 2019)
Acid-base titration method has been applied to detonation nanodiamond (DND) powder to determine active site functional groups attached on DND surfaces for de-aggregation of DND powders using different functionalization techniques. The UV/Ozone treated DND containing carboxylic group on its surface, tri-ethylene-tetra-amine (TETA) having ammine functionality, and ball milling treatment using ammonium bicarbonate as de-agglomerating and functionalizing media for ammine group attachment, are the functionalization techniques applied to DND powder. Functionalization and morphology of DND samples were characterized by XRD, SEM, RBS, ERDA and FTIR, while for measuring de-agglomeration and particle size distribution we performed dispersion tests and DLS of DND in three different solvent media. During investigation, the amount of carboxylic acid in the UV/Ozone functionalized DND sample has been observed to be 0.3 and 0.25 mM (milli moles) on the surface of DND powder with mole percentage of 1.28 and 2.86 % in the forward and backward titrations respectively. Similarly, the amount of ammine group (NH2) in TETA and ball-milling treatment has been observed to be 4 and 5 mM with mole percentages of 0.35 and 0.49 % respectively. Results showed that ball-milling treatment provides superior results and de-aggregation of DND powders.